Exceptional influenza morbidity in summer season of 2017 in Israel may predict the vaccine efficiency in the coming winter. Issue 11 (7th March 2018) - Pando, Rakefet; Sharabi, Sivan; Mandelboim, Michal
Highlights: In the 2017 summer, dozens of hospitalized patients were infected with influenza. Infections were due to influenza B (mostly B/Yamagata) and influenza A/H3N2. We predict that these two viruses will circulate in the coming winter of 2017/18. The yearly vaccine that includes antigenically different viruses might be inefficient. Abstract: Influenza infections are the leading cause of respiratory viral infections worldwide, and are mostly common in the winter season. The seasonal influenza vaccine is currently the most effective preventive modality against influenza infection. Immediately following each winter season the World Health Organization (WHO) announces the vaccine composition for the following winter. Unexpectedly, during the summer of 2017, in Israel, we observed in hospitalized patients, an exceptionally high numbers of Influenza positive cases. The majority of the influenza B infections were caused by influenza B/Yamagata lineage, which did not circulate in Israel in the previous winter, and most of the influenza A infections were caused by influenza A/H3N2, a strain similar to the strain that circulated in Israel in the previous winter. We therefore predict that these two viruses will circulate in the coming winter of 2017/18 and that the trivalent vaccine, which includes antigenically different viruses will be inefficient.